2018
DOI: 10.1111/epi.14505
|View full text |Cite
|
Sign up to set email alerts
|

The expression of inflammatory markers and their potential influence on efflux transporters in drug‐resistant mesial temporal lobe epilepsy tissue

Abstract: To the best of our knowledge, this study is the first to measure the cellular expression of COX-1, COX-2, and TSPO in microglia, astrocytes, and neurons in surgical brain tissue samples from patients with drug-resistant MTLE. Further research is needed to determine the effects of the COX inflammatory pathway in epilepsy, and how it relates to the expression of the ABC transporters P-gp and BCRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 30 publications
4
32
1
1
Order By: Relevance
“…Pre-treatment with the transcriptional as well as translational inhibitors showed no reduction in glutamate-induced COX-2 activity confirming the effect of glutamate on COX-2 to be independent of any transcriptional and translational changes. Contrary to our findings, previous preclinical 34,37,38 and clinical [51][52][53][54] studies have reported overexpression of COX-2 in brain and brain endothelial cells following seizures or in epilepsy. Epileptogenesis is a complex, multifactorial mechanism involving alterations in inhibitory and excitatory neurotransmitters, ion channels, neuroinflammatory pathways, etc., therefore, the effect on a particular gene may differ with the type of convulsive challenge to in vitro and in vivo model systems.…”
Section: Discussioncontrasting
confidence: 99%
“…Pre-treatment with the transcriptional as well as translational inhibitors showed no reduction in glutamate-induced COX-2 activity confirming the effect of glutamate on COX-2 to be independent of any transcriptional and translational changes. Contrary to our findings, previous preclinical 34,37,38 and clinical [51][52][53][54] studies have reported overexpression of COX-2 in brain and brain endothelial cells following seizures or in epilepsy. Epileptogenesis is a complex, multifactorial mechanism involving alterations in inhibitory and excitatory neurotransmitters, ion channels, neuroinflammatory pathways, etc., therefore, the effect on a particular gene may differ with the type of convulsive challenge to in vitro and in vivo model systems.…”
Section: Discussioncontrasting
confidence: 99%
“…BBB dysfunction is associated with Pgp induction in brain vessels and astrocytes and with increased COX-2 protein and prostaglandin (PG) E2 levels in the same epileptogenic regions (Bauer et al, 2008;Zibell et al, 2009;Schlichtiger et al, 2010;van Vliet et al, 2010). A strict association between COX-2 expression in neurons and glia, COX-1 expression in microglia, and increased Pgp and BCRP expression in microvessels was recently reported in surgical brain tissue from patients with drug-resistant mesial TLE (Weidner et al, 2018). The EP1 receptor (EP1R) for PGE2 seems to be a key factor mediating the COX-2 induced upregulation of Pgp.…”
Section: H Neuroinflammation and Blood-brain Barrier Dysfunction As mentioning
confidence: 92%
“…TSPO PET has been used to monitor neuroinflammation in numerous preclinical models and clinical cases of neurologic disease and injury (Dupont et al, 2017;Owen and Matthews, 2011), including epilepsy (Bertoglio et al, 2017). These studies have demonstrated that the contribution of different cell types to the TSPO PET signal can vary widely across diseases and models (Lavisse et al, 2012;Nguyen et al, 2018;Weidner et al, 2018;Yamasaki et al, 2017), highlighting the need to validate TSPO PET data to histological characterization neuroinflammation in individual models. There are currently no data evaluating the correspondence of TSPO PET imaging to histologic indices of neuroinflammation in any model of acute OP intoxication.…”
mentioning
confidence: 99%